MODERN ACCULTURAL PROCESSES AND VIEWS OF RUSSIAN KOREANS IN PERM KRAI ON FAMILY LIFE AND THEIR OWN IDENTITY - Kamenskikh, M.S. (Perm Federal Research Centre Journal, 2016)
The article presents main conclusions, based on the results of the field research among Russian Koreans in Perm Krai in 2012-2014. In particular, Koreans’ views on the language, family life and their own identity are considered.